A 20 m.y. long-lived successive mineralization in the giant Dahutang W–Cu–Mo deposit, South China - Song, W.; Yao, J.; Chen, H.; Sun, W.; Lai, C.; Xiang, X.; Luo, X.; Jourdan, Fred (Elsevier Science BV, 2018)
The connection between prolonged granitic magmatism and the formation of giant tungsten (W) polymetallic deposits has long been disputed. In this study, we present 6 mica Ar–Ar plateau ages and 22 molybdenite Re–Os model ages data on the newly discovered giant Dahutang W–Cu–Mo deposit in South China, which is one of the largest W deposits in the world. New and published zircon U–Pb, mica Ar–Ar, and molybdenite Re–Os age data reveal that the Mesozoic Dahutang magmatism and mineralization occurred in two major periods: (1) the Late Jurassic (ca. 153–147 Ma), forming the hydrothermal breccia, large wolframite-bearing quartz vein, and scheelite-dominated disseminated/veinlet type orebodies, which is mainly associated with the emplacement of porphyritic biotite granite; (2) the Late Jurassic to Early Cretaceous (ca. 146–130 Ma), forming the Cu–Mo–W ± Sn mineralization overprinting the Late Jurassic W–Mo ± Cu orebodies, which is mainly related to the successively emplacement of the Early Cretaceous granites. We suggest that continuous accumulation of mineralization for a long period of time (151–130 Ma) have contributed to the formation of the giant Dahutang deposit.